2018
DOI: 10.1016/j.chb.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Student profiling in a dispositional learning analytics application using formative assessment

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 30 publications
3
73
1
3
Order By: Relevance
“…Jeno and colleagues (2017) found that technology-enhanced feedback improved learning and well-being when feedback was related to 3 / 15 competence. Tempelaar, Rienties, Mittelmeier and Nguyen (2018) concluded that learning analytics and profiling help to identify learners needing support and to tailor efficient technology-enhanced feedback.…”
Section: Technology-enhanced Feedbackmentioning
confidence: 99%
“…Jeno and colleagues (2017) found that technology-enhanced feedback improved learning and well-being when feedback was related to 3 / 15 competence. Tempelaar, Rienties, Mittelmeier and Nguyen (2018) concluded that learning analytics and profiling help to identify learners needing support and to tailor efficient technology-enhanced feedback.…”
Section: Technology-enhanced Feedbackmentioning
confidence: 99%
“…To this framework, we have added Academic buoyancy from a later publication (Martin and Marsh, 2008). See Tempelaar et al (2015Tempelaar et al ( , 2018 for further elaboration.…”
Section: How Does Academic Motivation Based Upon Self-determination Imentioning
confidence: 99%
“…Students are positioned in the spectrum from self-regulation as the main mechanism, to external regulation. The scales are Selfregulation of learning processes and learning content, External-regulation of learning processes and learning results, and Lack of regulation (Tempelaar et al, 2015(Tempelaar et al, , 2018Vermunt, 1996). RQ2 What learning dispositions act as antecedents for these timing decisions, in other words students' learning regulation?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers in (Atherton et al, 2017) discussed the importance of tracing the physical movements to be incorporated in the learning analytics in order to achieve better understanding of in-class activities. Mirella Atherton et al (Tempelaar et al, 2018) conducted the study aimed at finding the correlation between the online study approach and its positive effects on attainments of the learners. Dirk Tempelar et al (Ravi et al, 2017) provided an empirical study aimed at showcasing how "learning decomposition data" can be used to deliver (Walker, 2012) proposed a methodology using the deep learning techniques to capture sensor data and perform analysis to predict real time activity classification.…”
Section: Related Work In Briefmentioning
confidence: 99%